Proton pump inhibitor prescribing patterns in the UK: a primary care database study. Issue 9 (3rd June 2016) - Othman, Fatmah; Card, Timothy R.; Crooks, Colin J.
Abstract: Purpose: To determine the prevalence and pattern of proton pump inhibitor (PPI) prescription and the practices employed to reduce PPI use in the UK general population. Methods: The UK's Clinical Practice Research Database was used to identify individuals who were issued with ≥1 PPI prescription during the period 1990–2014. Point and period prevalence of PPI use were estimated annually. Additionally, new users of PPI therapy who had 5 years of follow‐up data were included in a cohort analysis to describe patterns of cessation and duration of PPI use. Results: Both the period and point prevalence of PPI use increased between 1990 and 2014 (period prevalence increased from 0.2 to 15.0% and point from 0.03 to 7.7%). A total of 596 334 new users of PPI therapy in the cohort study received 8 784 272 prescriptions. Of these, 26.7% used PPI therapy long term (≥1 year continuously), while 3.9% remained on PPI therapy for 5 years. Clear attempts to step down dose were identified in 39.9% of long‐term users, while this was 47% in patients whose initial indication did not mandate long‐term use. Conclusion: A considerable increase in PPI use was observed in UK general practice. Of long‐term PPI users, 60% did not have an attempt to discontinue or step down. Considerable opportunities may therefore exist to reduce the cost and side effects of PPI use through improving adherence to recommended withdrawal strategies. Copyright © 2016 John Wiley & Sons, Ltd.